2023
DOI: 10.1007/s00170-023-10970-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced safety implementation in 5S + 1 via object detection algorithms

Abstract: Scholarly work points to 5S+1, a simple yet powerful method of initiating quality in manufacturing, as one of the foundations of Lean manufacturing and the Toyota Production Systems. The 6 th S, safety, is often used to prevent future occupational hazards, therefore, reducing the loss of time, money, and human resources. This paper aims to show how Industry 4.0 technologies such as computer-based vision and object detection algorithms can help implement the 6 th S in 5S+1 through monitoring and detecting worke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…For example, Kim and Lee (2023) discussed the relevance of ML and human–robot collaboration in the shift from lean production to mass customization, whereas Marinelli (2022) suggested that ML is crucially important for the intuitiveness of the collaboration between humans and robots. In terms of worker wellbeing, Shahin et al (2023e) presented a vision system and ML to verify workers’ compliance with the use of personal protective equipment requirements, such as safety helmets and safety vests.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kim and Lee (2023) discussed the relevance of ML and human–robot collaboration in the shift from lean production to mass customization, whereas Marinelli (2022) suggested that ML is crucially important for the intuitiveness of the collaboration between humans and robots. In terms of worker wellbeing, Shahin et al (2023e) presented a vision system and ML to verify workers’ compliance with the use of personal protective equipment requirements, such as safety helmets and safety vests.…”
Section: Resultsmentioning
confidence: 99%
“…This approach improves efficiency, reduces costs, ensures safety, and enables more effective decision-making based on comprehensive data analysis. The integration of Artificial Intelligence of Things (AIoT), Augmented Reality (AR), Virtual Reality (VR), and digital twins into this framework represents a significant advancement in utilizing big data and automation to support complex decision-making processes in infrastructure management [92][93][94].…”
Section: Remote Sensingmentioning
confidence: 99%
“…This method includes elements as shown in Figure 2, with the goal of eliminating waste and increasing production. The application of this method has been proven to minimize defect rates, increase equipment availability and improve operational safety (Shahin et al. , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%